L’analyse réflexive collective de l’activité de cadres de direction dans une relation de service « centrée sur autrui » - un cas de formation-action ergonomique dans le secteur des « crèches » municipales en France - Rafaël González (Perspectives Interdisciplinaires sur le Travail et la Santé)
The purpose of this paper is to describe how ergonomic action training in the collective reflective analysis of supervisors in daycare centers in a territorial community in France raised awareness about some of their activities and allowed them to be recognized, in particular by local politicians and administrative staff in the municipality. With this approach, the working conditions of all of the personnel were improved and changes to the organization of the early childhood care sector were proposed.